2008
DOI: 10.1186/1746-1340-16-10
|View full text |Cite
|
Sign up to set email alerts
|

How can chiropractic become a respected mainstream profession? The example of podiatry

Abstract: BackgroundThe chiropractic profession has succeeded to remain in existence for over 110 years despite the fact that many other professions which had their start at around the same time as chiropractic have disappeared. Despite chiropractic's longevity, the profession has not succeeded in establishing cultural authority and respect within mainstream society, and its market share is dwindling. In the meantime, the podiatric medical profession, during approximately the same time period, has been far more successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 36 publications
0
71
0
3
Order By: Relevance
“…[15][16][17][18][19][20] The chiropractic profession reportedly has been viewed as having poor ethics and dishonesty when compared to other health care professions. 21 Organizations and authors have identified the lack of integration with mainstream health care as a major challenge for the chiropractic profession and have suggested strategies to overcome this barrier. [21][22][23] Proposed strategies included chiropractors focusing on public health initiatives, chiropractic educational reform, interdisciplinary training, and interprofessional collaboration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20] The chiropractic profession reportedly has been viewed as having poor ethics and dishonesty when compared to other health care professions. 21 Organizations and authors have identified the lack of integration with mainstream health care as a major challenge for the chiropractic profession and have suggested strategies to overcome this barrier. [21][22][23] Proposed strategies included chiropractors focusing on public health initiatives, chiropractic educational reform, interdisciplinary training, and interprofessional collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…21 Organizations and authors have identified the lack of integration with mainstream health care as a major challenge for the chiropractic profession and have suggested strategies to overcome this barrier. [21][22][23] Proposed strategies included chiropractors focusing on public health initiatives, chiropractic educational reform, interdisciplinary training, and interprofessional collaboration. [21][22][23] One potential barrier to the integration of chiropractic into mainstream health care has been the negative perceptions of physicians towards chiropractic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Scholars have pointed out that the absence of a university-style tradition, coupled with a lack of access to government funding, has acted as a barrier to the development of the chiropractic profession. 32,33 The chiropractic teachers experienced their program as having been built, over several decades, independently of the large publicly funded university tradition, with all its pros and cons. Hence, the teachers' experience was that the program has had to rely exclusively on its own resources, thus developing a dandelion profession that managed on its own.…”
Section: Discussionmentioning
confidence: 99%
“…4 For decades, authors from within the chiropractic profession have called for the development of formally trained chiropractic researchers. 5 One factor in this change is that as new chiropractic teaching institutions around the world are being created within existing universities, the opportunities for research training and mentorship are increasing.…”
Section: Introductionmentioning
confidence: 99%